Answer: infinite answers, jk there is like a lot tho
Step-by-step explanation: The sum of x and y is 79. In other words, x plus y equals 79 and can be written as equation A:
x + y = 79
The difference between x and y is 23. In other words, x minus y equals 23 and can be written as equation B:
x - y = 23
Now solve equation B for x to get the revised equation B:
x - y = 23
x = 23 + y
Then substitute x in equation A from the revised equation B and then solve for y:
x + y = 79
23 + y + y = 79
23 + 2y = 79
2y = 56
y = 28
Now we know y is 28. Which means that we can substitute y for 28 in equation A and solve for x:
x + y = 79
x + 28 = 79
X = 51
Summary: The sum of the two numbers is 79 and their difference is 23. What are the two numbers? Answer: 51 and 28 as proven here:
Sum: 51 + 28 = 79
Difference: 51 - 28 = 23
Please give me brainliest
Answer:
5 ( x + 69)/4
Step-by-step explanation:
Answer:
12 which is on C
Step-by-step explanation:
use pathogoras theorem
a^2+b^2=c^2
16^2+b^2=20^2
256+b^2=400
b^2=400-256
b^2=144
b= square root of 144
b= 12
Answer:
a is 3,2 b is 1,-2 and c is -2,1
Step-by-step explanation:
u take the first number then you just put em together